Nigeria - Design of the Community Social Development Project (CSDP) - Watkins, Sharon L. (World Bank, Washington, DC, 2012)
The concept review for the Nigeria Community Social Development Project (CSDP) began in March 2005 with project appraisal scheduled for early 2006. The design of the CSDP incorporates innovative elements in Community Driven Development from Community-based Poverty Reduction Project (CPRPI) and is expected to play a pivotal role in harmonizing Community Driven Development (CDD) activities in Nigeria.